2017
DOI: 10.1002/cnm.2939
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the left ventricular size and the amount of trabeculations

Abstract: Contemporary imaging modalities offer noninvasive quantification of myocardial deformation; however, they make gross assumptions about internal structure of the cardiac walls. Our aim is to study the possible impact of the trabeculations on the stroke volume, strain, and capacity of differently sized ventricles. The cardiac left ventricle is represented by an ellipsoid and the trabeculations by a tissue occupying a fixed volume. The ventricular contraction is modeled by scaling the ellipsoid whereupon the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…Reduced global systolic function might be caused by increased meridional wall stress in the more spherical ventricle. In our study, deformation in spherical ventricles was more load dependent compared to more ellipsoid‐shaped ones, indicating that the ellipsoid shape compensates for increasing afterload, while the spherical ventricles do not …”
Section: Discussionmentioning
confidence: 50%
“…Reduced global systolic function might be caused by increased meridional wall stress in the more spherical ventricle. In our study, deformation in spherical ventricles was more load dependent compared to more ellipsoid‐shaped ones, indicating that the ellipsoid shape compensates for increasing afterload, while the spherical ventricles do not …”
Section: Discussionmentioning
confidence: 50%
“…Both studies lead to the discovery of the same loci, indicating that FD associations are independent of ventricular size. To replicate our findings we analysed the independent cohort of 1,129 people, applied the same image analysis pipeline and ran an equivalent genetic association study (10,673,171 genetic variants). As expected given the lower sample size, few of the associations passed a genome-wide threshold, however nearly all the estimates of effect direction were concordant (91% of comparisons concordant) between the two studies (correlation of beta estimates: r 2 = 0.516, Figure 13 in the Supplement).…”
Section: Mainmentioning
confidence: 78%
“…8,9 However, the role of trabeculae in the ventricular mechanics of healthy adults and why such a critical compartment of the cardiovascular system retains a complex inner surface is unclear. Theoretical analyses have shown that an absence of trabeculae requires greater strain to maintain cardiac output, 10 and it has been proposed that their complex structure contributes to efficient intra-ventricular flow patterns. 11,12 Progress in understanding the functional role of organ components often relies on observing changes during physiological experiments or by identifying genes that selectively influence relevant morphology.…”
Section: Mainmentioning
confidence: 99%
“…Paun et al studied the effect of LV trabeculations on ventricular performance and size using computational modelling. They demonstrated that in a smooth, non-trabeculated LV, increases in stroke volume came at considerable energetic cost, requiring increasingly high longitudinal strain, whereas a trabeculated LV was capable of achieving high stroke volumes without incurring exponential elevations in strain [ 13 ]. Both of these studies, however, have important limitations in mathematical oversimplification of left ventricular geometry, viscoelastic properties of trabeculae and myocardial deformation.…”
Section: Potential Role Of Increased Trabeculae In Cardiac Adaptationmentioning
confidence: 99%